EFFICIENCY OF STUDENTS PASSING THE GTO STANDARD "16 KG KETTLEBELL SNATCH" AFTER THE INTRODUCTION OF ADVANCED SPECIALIZATION IN KETTLEBELL SPORT - Kataev I.V.; Kolesnikov N.V.; Striga S.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to evaluate the effectiveness of students’ performance of the GTO standard "16 kg kettlebell snatch" after the introduction of the specialization "Kettlebell lifting". Methods and structure of the study. The following research methods were used in the work: literature review, mathematical processing of research results, data collection. Using the example of data on passing the GTO standards for snatching a 16 kg kettlebell, an analysis of the dependence of the results on the introduction of the specialization is carried out. Results and conclusions. The obtained achievements indicate a positive impact of the strategy of introducing the specialization "Kettlebell lifting" on increasing the level of physical quality "strength" of students.